Learning and engagement through natural history museums - Mujtaba, Tamjid; Lawrence, Martin; Oliver, Mary; Reiss, Michael (Taylor & Francis, 2018)
This review examines how natural history museums (NHMs) can enhance learning and engagement in science, particularly for school-age students. First, we describe the learning potential of informal science learning institutions in general, then we focus on NHMs. We review the possible benefits of interactions between schools and NHMs, and the potential for NHMs to teach about challenging issues such as evolution and climate change and to use digital technologies to augment more traditional artefacts. We conclude that NHMs can provide students with new knowledge and perspectives, with impacts that can last for years. Through visits and their on-line presence, NHMs can help students see science in ways that the school classroom rarely can, with opportunities to meet scientists, explore whole topic exhibitions, engage with interactive displays and employ digital technologies both in situ and to support learning in the school science classroom. Although these interactions have the potential to foster positive cognitive, affective and social outcomes for students, there is a lack of reliable measures of the impact of NHM experiences for students. Opportunities to foster relationships between NHM staff and teachers through professional development can help articulate shared goals to support students’ learning and engagement.